Squamous Cell Carcinoma following Epidermoid Cyst in the Buttock. Issue 2 (February 2019) - Niimi, Yosuke; Takeuchi, Masaki; Isono, Nobuo
Abstract : Summary: In the field of plastic surgery, subcutaneous masses in the buttocks are frequently observed. However, squamous cell carcinoma (SCC) after epidermoid cyst, which appears in the presacral space, is extremely rare. This report described a case of a 71-year-old woman, who previously received a skin incision by a doctor for treating a cystic lesion in the buttock; she was diagnosed with SCC by preoperative biopsy at the authors' department. In addition, computed tomography suspected that the tumor originated in the presacral space. Under general anesthesia, an extended resection of the malignant tumor with gastrointestinal surgery was performed. After resection, the defect of buttocks region was reconstructed with a V-Y advancement gluteus maximus myocutaneous flap. After pathological examination the tumor was diagnosed as SCC after epidermoid cyst; peplomycin sulfate at 50 mg/d was administered intramuscularly for 2 weeks as chemotherapy. No wound complications were observed after surgery, and no recurrence was noted for 5 years. For managing tumor in the gluteal region, a possibility of malignancy must be considered, and thorough radiographic studies must be pursued before surgery. Abstract : Supplemental Digital Content is available in the text.